Handbook of research on green ICT technology, business and social perspectives - Unhelkar, Bhuvan (Hershey, Pennsylvania Information Science Reference, 2011)
"This handbook coalesces worldwide investigations, thoughts, and practices in the area of Green ICT, covering the technical advances, methodological innovations, and social changes that result in enhancements and improvements in business strategies, social policies, and technical implementations"--Provided by publisher.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Business enterprises -- Environmental aspects; Strategic planning -- Environmental aspects; Technological innovations -- Environmental aspects; Social change